Efforts to Improve Math Learning Result of Fourth Grade Students Through Contextual Model Teaching and Learning with Cuisenaire Rods Media - Intan Kurnia Sari; Tri Nova Hasti Yunianta (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2017)
The purpose of this research is to improve students' learning outcomes in mathematics learning through Contextual Teaching and Learning (CTL) model with Cuisenaire Rods media in grade IV Dukuh 03 Salatiga Elementary School semester II year 2015/2016. This research was conducted to help teachers who still used conventional methods and had not yet maximized learning media in the classroom. This research is a classroom action research that consists of two cycles. Each cycle consists of four phases: planning, implementation, observation, and reflection. The subjects of this study were 26 students. Data collection techniques used in this study were observation, testing, and documentation. The instruments used were test items, the student activity and teacher observation sheet. Data analysis was performed by using a comparative descriptive analysis by comparing the results of pre-cycle, the first cycle, and the second cycle. The indicator of success in this study was that 75% students reaching the score of ≥ 64. The research showed an increase in the value of the average grade from 61.77 in the pre-cycle to 78 in the first cycle and up to 85 in the second cycle. The number of students who passed the study increased from 11 students (42.31%) in the pre-cycle to 20 students (76.92%) in the first cycle and up to 24 students (92.31%) in the second cycle, so it can be concluded that the application of Contextual Teaching and Learning (CTL) model using Cuisenaire Rods media can improve students' learning outcomes in mathematics in the area of adding and subtracting fractions with the same denominator and with different denominators.